Choosing Appropriate Contract Methods for Design-Build Projects - Chen, Q.; Xia, B.; Jin, Z.; Wu, Peng; Hu, Y. (2016)
For design-build (DB) projects, owners normally use lump sum and guaranteed maximum price (GMP) as the major contract payment provisions. However, there was a lack of empirical studies to compare the project performance within different contract types and investigate how different project characteristics affect the owners’ selection of contract arrangement. Project information from the Design-Build Institute of America database was collected to reveal the statistical relationship between different project characteristics and contract types and to compare project performance between lump sum and GMP contract. The results show that lump sum is still the most frequently used contract method for DB projects, especially in the public sector. However, projects using GMP contract are more likely to have less schedule delay and cost overrun as compared to those with lump-sum contracts. The chi-square tests of cross tabulations reveal that project type, owner type, and procurement method affect the selection of contract types significantly. Civil infrastructure rather than industrial engineering project tends to use lump sum more frequently, and the qualification-oriented contractor selection process resorts to GMP more often compared with the cost-oriented process. The findings of this research contribute to the current body of knowledge concerning the effect of associated project characteristics on contract type selection. Overall, the results of this study provide empirical evidence from real DB projects that can be used by owners to select appropriate contract types and eventually improve future project performance.